Alternative Fistula Risk Score for Pancreatoduodenectomy (a-FRS): Design and International External Validation. Issue 5 (May 2019) - Mungroop, Timothy H.; van Rijssen, L. Bengt; van Klaveren, David; Smits, F. Jasmijn; van Woerden, Victor; Linnemann, Ralph J.; de Pastena, Matteo; Klompmaker, Sjors; Marchegiani, Giovanni; Ecker, Brett L.; van Dieren, Susan; Bonsing, Bert; et al.
Abstract : Objective: The aim of this study was to develop an alternative fistula risk score (a-FRS) for postoperative pancreatic fistula (POPF) after pancreatoduodenectomy, without blood loss as a predictor. Background: Blood loss, one of the predictors of the original-FRS, was not a significant factor during 2 recent external validations. Methods: The a-FRS was developed in 2 databases: the Dutch Pancreatic Cancer Audit (18 centers) and the University Hospital Southampton NHS. Primary outcome was grade B/C POPF according to the 2005 International Study Group on Pancreatic Surgery (ISGPS) definition. The score was externally validated in 2 independent databases (University Hospital of Verona and University Hospital of Pennsylvania), using both 2005 and 2016 ISGPS definitions. The a-FRS was also compared with the original-FRS. Results: For model design, 1924 patients were included of whom 12% developed POPF. Three predictors were strongly associated with POPF: soft pancreatic texture [odds ratio (OR) 2.58, 95% confidence interval (95% CI) 1.80–3.69], small pancreatic duct diameter (per mm increase, OR: 0.68, 95% CI: 0.61–0.76), and high body mass index (BMI) (per kg/m 2 increase, OR: 1.07, 95% CI: 1.04–1.11). Discrimination was adequate with an area under curve (AUC) of 0.75 (95% CI: 0.71–0.78) after internal validation, and 0.78 (0.74–0.82) after external validation. The predictive capacity of a-FRS was comparable with the original-FRS, both for the 2005 definition (AUC 0.78 vs 0.75, P = 0.03), and 2016 definition (AUC 0.72 vs 0.70, P = 0.05). Conclusion: The a-FRS predicts POPF after pancreatoduodenectomy based on 3 easily available variables (pancreatic texture, duct diameter, BMI) without blood loss and pathology, and was successfully validated for both the 2005 and 2016 POPF definition. The online calculator is available at www.pancreascalculator.com .